2010
DOI: 10.1007/s13139-010-0039-7
|View full text |Cite
|
Sign up to set email alerts
|

CpG Oligodeoxynucleotides Enhance the Activities of CD8+ Cytotoxic T-Lymphocytes Generated by Combined hMUC1 Vaccination and hNIS Radioiodine Gene Therapy

Abstract: Purpose The authors evaluated whether the cytotoxicity of CD8+CTLs generated by combined hMUC1 vaccination and hNIS radioiodine gene therapy was enhanced in the presence of CpG in an established tumor model. Methods CMNF cells (CT26 cells expressing hMUC1, hNIS and Firefly luciferase) were transplanted into BALB/c mice. Four and 10 days later, tumor-bearing mice were immunized intramuscularly with pcDNA3.1 or pcDNA-hMUC1 or pcDNA-hMUC1+CpG, and subsequently administered PBS or 131 I [five groups (seven mice/gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Most importantly, these methods allow researchers to non-invasively monitor the proliferation and migration of infused cells, which are important aspects of cell-based therapy in living subjects. Similar to the luciferase and HSV1-tk genes that are extensively investigated for their use in cell tracking, the NIS gene has also been demonstrated to be an attractive reporter gene for monitoring cancer progression and therapeutic response 6 , stem cell trafficking 8 , and specific cellular events 0 in living subjects. Recently, several studies have demonstrated the possibility of using the NIS gene as a reporter for the tracking of T cells and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, these methods allow researchers to non-invasively monitor the proliferation and migration of infused cells, which are important aspects of cell-based therapy in living subjects. Similar to the luciferase and HSV1-tk genes that are extensively investigated for their use in cell tracking, the NIS gene has also been demonstrated to be an attractive reporter gene for monitoring cancer progression and therapeutic response 6 , stem cell trafficking 8 , and specific cellular events 0 in living subjects. Recently, several studies have demonstrated the possibility of using the NIS gene as a reporter for the tracking of T cells and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Boccacio et al have demonstrated that non-coding plasmid DNA inhibits experimental allergic encephalomyelitis via the activation of IFN-γ [ 27 ]. CpG motifs have been used as an adjuvant to enhance the cellular responses in various disorders, such as cancer, and it has a significant immunostimulatory effect on the induction of cell death in cancer cells via activating cytotoxic T cells [ 49 ]. Bacterial CpG motif binds to toll-like receptor 9 (TLR-9), which is expressed by different immune system cells, such as macrophages, dendritic cells and natural killer (NK) cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial CpG motif binds to toll-like receptor 9 (TLR-9), which is expressed by different immune system cells, such as macrophages, dendritic cells and natural killer (NK) cells. This motif is known to activate lymphocytes and induce them to secrete a verity of cytokines, including IL-6, IL-12, and IFN-γ [ 49 ]. Quintana et al have reported that CpG motif is able to induce the expression of IFN-γ [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, since the NIS gene was first cloned in 1996 [26], many studies have demonstrated the efficacy of molecular imaging or radioiodide gene therapy using NIS in vitro and in vivo [16,17,[27][28][29]. NIS has a number of obvious advantages, such as, its potential use as a diagnostic gene for noninvasive imaging, the bystander effect due to crossfire by β-emitters, the lack of immune response due to its endogenous origin, its well-known physiological effects, and others [23].…”
Section: Discussionmentioning
confidence: 99%